Effectiveness of Superior Hypogastric Plexus Block for Pain Control Compared to Epidural Anesthesia in Women Requiring Uterine Artery Embolization for the Treatment of Uterine Fibroids – A Retrospective Evaluation - Malouhi, Amer; Aschenbach, Rene; Erbe, Anna; Owsianowski, Zbigniew; Rußwurm, Stefan; Runnebaum, Ingo B.; Teichgräber, Ulf (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Purpose To assess the effectiveness of pain management with superior hypogastric plexus block (SHPB) compared to epidural anesthesia (EDA) in women requiring uterine artery embolization (UAE).Materials and Methods In this retrospective, single-center, non-randomized trial we included 79 women with symptomatic uterine fibroids who were scheduled for percutaneous, transcatheter UAE. According to their informed decision, the women were assigned to two different approaches of pain management including either SHPB or EDA. The effectiveness outcome measure was patient reported pain using a numeric rating scale ranging from 1 to 10. The pain score was assessed at UAE, 2 hours thereafter, and at subsequent intervals of 6 hours up to 36 hours after intervention.Results Treatment groups did not differ significantly regarding age, pain score for regular menstrual cramps, uterine fibroid size, location, and symptoms of uterine fibroids. During UAE and up to 6 hours thereafter, women who received SHPB experienced stronger pain than those who received EDA (mean pain score during UAE: 3.3 vs. 1.5, p < 0.001; at 2 hours: 4.4 vs. 2.8, p = 0.012; at 6 hours: 4.4 vs. 2.6, p = 0.021). The maximum pain level was 5.8 ± 2.9 with SHPB and 4.5 ± 2.9 with EDA (p = 0.086). Women with a history of severe menorrhagia tended to experience worse pain than those without (regression coefficient 2.5 [95 % confidence interval –0.3 to 5.3], p = 0.076).Conclusion Among women who underwent UAE, pain management including SHPB resulted in stronger pain during and after the procedure than pain treatment including EDA.Key Points:Citation Format
Keywords: fibroids; interventional pain management; microspheres; nerve block; pelvic pain; superior hypogastric plexus